Literature Review of Cultural Distance in Tourism: A Bibliometric Approach - Nguyen Thi Thien, Trang; Nguyen Thi Cam, Le; Le Van, Hoa (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
In the context of increasingly deepening globalization, tourism not only plays an important socio-economic role but also acts as a driving force for sustainable development in many countries and territories. Along with the expansion of the scale and scope of international exchanges, issues related to cultural differences have increasingly attracted growing scholarly attention, in which cultural distance has emerged as a key topic in the tourism field. This study employs a bibliometric method, drawing on data from the Web of Science database and analyzing it with VOSviewer, to systematize and analyze the scholarly literature on cultural distance in tourism. This approach enables the determination of development trends in the field, academic structures, scholarly networks, and existing knowledge gaps. In addition, the study identified key themes shaping the scholarly literature on cultural distance in tourism, thereby suggesting future research directions to enhance theoretical understanding and practical application in multicultural contexts.
Keywords: Cultural distance; Travel; Tourists; Bibliometrics